Discoloration of Bulk-Fill versus conventional composites : a spectrophotometric evaluation = Decoloración de resinas Bulk vs resinas convencionales : evaluación espectrofotométrica - Serin Kalay, Tugba
Purpose: The purpose of this study was to evaluate the discoloration of a dual-cure bulk-fill (DCBF) and light-cure bulk-fill (LCBF) composites relative to conventional composites (CC) after water and coffee immersion. Methods: One-hundred disc-shaped specimens (8mm in diameter × 4mm thickness) were prepared using five commercially available composites (n=10); two LCBF (XB-X-trafil Voco, FB-FiltekTM Bulk Fill), one DCBF (FU-Fill-upTM Coltene), and two CC (CE-Clearfil Majesty ES2, EQ-Estelite ΣQuick). Initial and final color readouts were measured with a spectrophotometer (Easyshade,Vita) according to the CIELAB color system. Statistical analyses were performed using 2-way ANOVA with Bonferroni adjustment to evaluate ΔE, ΔL, Δa, and Δb parameters (p<0.05). Results: Significant interactions were noted among the material types and immersion solutions for all evaluated parameters (p=0.00). ΔE values were observed in the order of FU>FB≥XB>EQ≥CE in water immersion groups and XB>FB>EQ≥FU≥CE in coffee immersion groups. Conclusion: Within the limitations of this study, DCBF composite is more susceptible to intrinsic discoloration compared to LCBF and CC. However, DCBF exhibited lower extrinsic discoloration than LCBF and comparable with CC after coffee immersion. Depending on their chemical and structural compositions, composites will exhibit color change, which compromises the esthetic performance of composite restorations.